Coronary Calcification is More Predictive of Carotid Intimal Medial Thickness in Black Compared to White Middle Aged Men - El-Saed, Aiman (2007)
BACKGROUND: Race-specific data for the association between coronary artery calcification (CAC) and carotid intimal medial thickness (IMT) are limited. We sought to compare black-white specific associations of these two measures. METHODS: We conducted a population-based study of 379 randomly-selected men aged 40–49 years (84 black and 295 white) from Allegheny County, US (2004–2006). Agatston CAC score was evaluated by electron-beam tomography and carotid IMT was evaluated by ultrasonography. RESULTS: Compared to white men, black men had similar prevalence of CAC (p=0.56) and higher total carotid IMT (p<0.001). In black and white men, CAC score had significant positive correlations with total carotid IMT (r=0.47 & r=0.24 respectively, p<0.001 for both) as well as the IMT for the common carotid artery (CCA), internal carotid artery and carotid bulb. The associations of CAC with total and CCA IMT were significantly stronger in black (beta=0.07 & beta=0.05 respectively) than white men (beta=0.03 & beta=0.01 respectively) after adjustment for traditional coronary risk factors (p=0.046 & p=0.036 respectively). CONCLUSIONS: In black and white middle-aged men, CAC score had significant positive correlations with total and segmental carotid IMT. CAC was more predictive of total and CCA IMT in black than white men independent of coronary risk factors.